Honore de Balzac’s “The Unknown Masterpiece” and the Avant-garde Theory of Art - Rykov, Anatolii V. (Actual Problems of Theory and History of Art, 2024)
Skeptical and pragmatic concepts are becoming increasingly important in the context of the interpretation of avant-garde art. The article considers Honore de Balzac’s “The Unknown Masterpiece” as a key text for understanding the European theory of art. The pragmatic concept of avant-garde art is inextricably linked with the movement of theoretical thought from mannerism to the 19th century. Although both Romanticism and avant-garde art are often associated with enthusiastic versions of culture and art, more cynical and instrumental strategies within these trends cannot be excluded from our view. First of all, attention is drawn to the manipulative concepts of the art form (the recognition of its relativity) and the sociological concepts of art as entertainment. “The Unknown Masterpiece” uniquely combines the most radical utopian and pragmatic concepts of Romanticism. That is why it can be regarded as an important source of avant-garde pragmatic strategies. The “destructive” methods of the avant-garde are interpreted as “realistic”, anticipating later scientific strategies of deconstruction. The institutional and semiotic aspects of the image theory proposed by Balzac anticipate the concept of the formlessness invented by Yves-Alain Bois and Rosalind Krauss. The convergence of skeptical concepts of romantic and avant-garde cultures allows us to give a new interpretation of the history of contemporary art. The “manneristic” features of the sophisticated theoretical concepts of Balzac, Kandinsky, and Hugo Ball expand the field of iconological readings of abstractionism and Dadaism. The “musical” and the formless in the works of Balzac and Kandinsky turn out to be a mask for the deepest skepticism. Similar pragmatic discourses can be associated with the category of the fantastic in Balzac’s and Hugo Ball’s oeuvre.